2013
DOI: 10.1111/obr.12014
|View full text |Cite
|
Sign up to set email alerts
|

Risk of completed suicide after bariatric surgery: a systematic review

Abstract: Bariatric surgery is one of the most effective treatments for morbid obesity, and a large body of research indicates significant long-term weight loss. While overall mortality decreases in patients who received bariatric surgery, a number of studies have shown that suicide rates are higher in bariatric patients than in control groups. The objective of this study was to present a systematic review of suicide mortality after bariatric surgery and calculate an estimate for the suicide rate. Literature researches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(116 citation statements)
references
References 115 publications
4
100
0
9
Order By: Relevance
“…There may also be a role for enhanced psychological support to address postoperative mental health issues. More recently, studies have reported elevated suicide rates following bariatric surgery [74][75] in BS groups when compared to control groups [76].…”
Section: Discussionmentioning
confidence: 99%
“…There may also be a role for enhanced psychological support to address postoperative mental health issues. More recently, studies have reported elevated suicide rates following bariatric surgery [74][75] in BS groups when compared to control groups [76].…”
Section: Discussionmentioning
confidence: 99%
“…However, a lot of patients continue to suffer from emotional disturbances, mainly due to unrealistic pre-surgical expectations concerning weight loss and difficulties associated with the necessity of post-bariatric life style changes. Several studies have reported increased suicide incidence in patients after bariatric surgery, with an estimated suicide rate of 3.9/10 000, compared with 1.0/10 000 in the general population [55]. The most common reason found is depression, but the spectrum of mental disorders linked to suicidal ideation and attempts is wide.…”
Section: Behavioral and Psychological Supportmentioning
confidence: 99%
“…A recent study noted suicide rates after bariatric surgery to be five times that of general population [35]. The need for post-surgery follow-up specifically for depression should be emphasized [25,36].…”
Section: ]mentioning
confidence: 99%